PENGARUH FINANCIAL STABILITY, FINANCIAL TARGETS, NATURE OF INDUSTRY DAN INEFFECTIVE MONITORING TERHADAP FINANCIAL STATEMENT (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX) - Sari, Ika Kumala; Istutik, Istutik (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
This research aims to detect the financial statement Fraud by using analysis of fraud triangle. Based on the theory advanced by Donald R Cressey (1953) or the theory of Cressey, there are three conditions that are always present in the act of fraud, namely pressure, opportunity and rationalization which is referred to as the fraud triangle. These three conditions are risk factors for the incidence of fraud in various conditions. However, in this study only analyzed using the fraud triangle element variable pressures and opportunity, and do not use the variable element of rationalization. The variables used in this study consisted of each of the elements including the Financial Stability proxied by the ratio of the change in total assets (ACHANGE), financial targets proxied by Return on Assets (ROA), the nature of the industry which is proxied by the ratio of change in receivables (RECEIVABLE), and ineffective monitoring proxied by the ratio of independent directors (IND) and variable financial statement fraud proxied by the earnings management.The population in this study are a company listed in JII Company (Jakarta Islamic Index) and publish annual reports in a row duringÂ 2011-2015. The sampling technique is purposive sampling. Based on these criteria was selected 12 companies sampled in this study. The analysis used is multiple linear regression and SPSS 22 software using the results of testing tools.This study indicate that the Financial Stability variables, the financial targets, the nature of the industry a significant positive effect on the Financial Statement Fraud and Ineffective Monitoring while significant negative effect on the Financial Statement Fraud.